The experience of initiating injection drug use and its social context: a qualitative systematic review and thematic synthesis. (29th September 2017) - Guise, Andy; Horyniak, Danielle; Melo, Jason; McNeil, Ryan; Werb, Dan
Abstract: Background and aim: Understanding the experience of initiating injection drug use and its social contexts is crucial to inform efforts to prevent transitions into this mode of drug consumption and support harm reduction. We reviewed and synthesized existing qualitative scientific literature systematically to identify the socio‐structural contexts for, and experiences of, the initiation of injection drug use. Methods: We searched six databases (Medline, Embase, PsychINFO, CINAHL, IBSS and SSCI) systematically, along with a manual search, including key journals and subject experts. Peer‐reviewed studies were included if they qualitatively explored experiences of or socio‐structural contexts for injection drug use initiation. A thematic synthesis approach was used to identify descriptive and analytical themes throughout studies. Results: From 1731 initial results, 41 studies reporting data from 1996 participants were included. We developed eight descriptive themes and two analytical (higher‐order) themes. The first analytical theme focused on injecting initiation resulting from a social process enabled and constrained by socio‐structural factors: social networks and individual interactions, socialization into drug‐using identities and choices enabled and constrained by social context all combine to produce processes of injection initiation. The second analytical theme addressed pathways that explore varying meanings attached to injection initiation and how they link to social context: seeking pleasure, responses to increasing tolerance to drugs, securing belonging and identity and coping with pain and trauma. Conclusions: Qualitative research shows that injection drug use initiation has varying and distinct meanings for individuals involved and is a dynamic process shaped by social and structural factors. Interventions should therefore respond to the socio‐structural influences on injecting drug use initiation by seeking to modify the contexts for initiation, rather than solely prioritizing the reduction of individual harms through behavior change.